WENO Scheme-Based Lattice Boltzmann Flux Solver for Simulation of Compressible Flows (Communications in Computational Physics, 2020)
In this paper, the finite difference weighed essentially non-oscillatory(WENO) scheme is incorporated into the recently developed lattice Boltzmann fluxsolver (LBFS) to simulate compressible flows. The resultant WENO-LBFS schemecombines advantages of WENO scheme and LBFS, e.g., high-order accuracy, highresolution and physical robustness. Various numerical tests are carried out to comparethe performance of WENO-LBFS and that of other WENO-based flux solvers, includingthe Lax-Friedrichs flux, the modification of the Harten-Lax-van Leer flux, themulti-stage predictor-corrector flux and the flux limiter centered flux. It turns out thatWENO-LBFS is able to capture discontinuous profile in shock waves. Comparatively,the WENO-LBFS scheme costs less CPU time and eases programming.
Keywords: WENO scheme; lattice Boltzmann flux solver; numerical flux; shock wave; compressible flows.